CUSTOMER SATISFACTION AND ENVIRONMENTAL CONCERN BASED MULTIPLE OBJECTIVE OPTIMIZATION MODEL FOR SUSTAINABLE SUPPLY CHAIN IN REAL LIFE: AN INTUITIONISTIC FUZZY T-SET APPROACH - GARAI, ARINDAM; MONDAL, BAPPA; ROY, TAPAN K (International Journal of Mathematical Archive, 2018)
In this paper, one customer satisfaction and environmental concern based multiple objective optimization model is presented to manage supply chain under uncertainty. Although much ...